The - Kostof, Spiro (Oxford University Press Inc, 1995)
No mere survey of famous buildings, Kostof's History examines an inclusive spectrum of manmade structures: prehistoric huts and the TVA, the pyramids at Giza and the Rome railway station, the ziggurat and the department store. Indeed, Kostof considered every building worthy of attention, every structure or shelter a potential source of insight, whether it be the prehistoric hunting camps at Terra Amata, or the caves at Lascaux with their magnificent paintings, or a twenty-story hotel on the Las Vegas strip. The Second Edition features a new concluding chapter, "Designing the Fin-de-Siecle, " based on Kostof's last lecture notes and prepared by Castillo, as well as an all-new sixteen-page color section. Many of the original line drawings by Richard Tobias, as well as some fifty photographs, have also been updated or replaced, for improved clarity